2013
DOI: 10.1103/physrevlett.110.213002
|View full text |Cite
|
Sign up to set email alerts
|

Electron Localization Involving Doubly Excited States in Broadband Extreme Ultraviolet Ionization ofH2

Abstract: Dissociative single ionization of H 2 induced by extreme ultraviolet photons from an attosecond pulse train has been studied in a kinematically complete experiment. Depending on the electron kinetic energy and the alignment of the molecule with respect to the laser polarization axis, we observe pronounced asymmetries in the relative emission directions of the photoelectron and the H þ ion. The energydependent asymmetry pattern is explained by a semiclassical model and further validated by fully quantum mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Recent studies showed how femtosecond VUV and XUV radiation can be used to reveal transient nuclear and electron dynamics in diatomic molecules [8][9][10][11][12] as well as in more complex molecular systems [13,14]. To probe such dynamics, the majority of the pump-probe-style experiments accomplished to date utilize not only pairs of XUV-IR pulses [8,[15][16][17][18], but also a combination of VUV-XUV pulses [19][20][21][22]. These experiments have led to the observation of novel ultrafast phenomena in molecules and have allowed for the temporal characterization of known dissociation processes [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed how femtosecond VUV and XUV radiation can be used to reveal transient nuclear and electron dynamics in diatomic molecules [8][9][10][11][12] as well as in more complex molecular systems [13,14]. To probe such dynamics, the majority of the pump-probe-style experiments accomplished to date utilize not only pairs of XUV-IR pulses [8,[15][16][17][18], but also a combination of VUV-XUV pulses [19][20][21][22]. These experiments have led to the observation of novel ultrafast phenomena in molecules and have allowed for the temporal characterization of known dissociation processes [21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, time-domain studies can elucidate the dynamic nature of correlations driving ultrafast charge dynamics in molecules and can open the door for the direct control of reaction pathways. Attosecond and femtosecond XUV pulses based on nonlinear high-harmonic generation (HHG) offer sufficiently broad bandwidths, forming an ideal tool for probing electronic superpositions in a wide variety of systems [5,6,11,12]. However, these techniques have not been applied in the pump-probe studies of coherent charge dynamics in polyatomic systems that exhibit complex behavior near conical intersections.…”
mentioning
confidence: 99%
“…Therefore, the natural time scale for charge motion lies in the attosecond to femtosecond regime. Recent developments in attosecond, extreme ultraviolet (XUV) science provide new opportunities for the real-time investigation of electron dynamics in atomic [3][4][5][6] and molecular systems [7][8][9][10][11][12][13]. Specifically, by virtue of the high photon energy, ultrafast XUV pulses allow access to electron hole dynamics in photoionized molecules, an unexplored class of charge transfer phenomena [14][15][16].…”
mentioning
confidence: 99%
“…Write Attention: PRA Project Manager and the Article ID, XH10238A, on the proof copy unless it is already printed on your proof printout. by steering the reaction with unprecedented precision [19][20][21][22][23].…”
Section: Ways To Respondmentioning
confidence: 99%